2019
DOI: 10.3847/2041-8213/ab44ce
|View full text |Cite
|
Sign up to set email alerts
|

Energy Budgets for Terrestrial Extrasolar Planets

Abstract: The pathways through which incoming energy is distributed between the surface and atmosphere has been analyzed for the Earth. However, the effect of the spectral energy distribution of a host star on the energy budget of an orbiting planet may be significant given the wavelength-dependent absorption properties of atmospheric CO 2 and water vapor, and surface ice and snow. We have quantified the flow of energy on aqua planets orbiting M-, G-, and F-dwarf stars, using a 3D Global Climate Model with a static ocea… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…Consistent with a sun-like star irradiance, the planet surface absorbs ≈ 48% of the incoming SW radiation. This number would decrease for a red dwarf star because the planet atmosphere would absorb a larger amount of SW radiation (Shields et al (2019)).…”
Section: Surface Energy Budgetmentioning
confidence: 99%
“…Consistent with a sun-like star irradiance, the planet surface absorbs ≈ 48% of the incoming SW radiation. This number would decrease for a red dwarf star because the planet atmosphere would absorb a larger amount of SW radiation (Shields et al (2019)).…”
Section: Surface Energy Budgetmentioning
confidence: 99%
“…This is due to the wavelength dependence of the ice albedo, which decreases with wavelength above 0.5 µm, leading to a lower contrast between ice and water (Joshi & Haberle 2012). Shields et al (2019) took this further to find that a planet orbiting an M dwarf absorbs 12% more incident solar energy than its G dwarf counterpart for an Earth-like configuration with a 24-hour rotational period. Meanwhile, Yang et al (2019a) found that an increase in atmospheric absorption of stellar radiation led to an increase in relative humidity at higher altitudes globally, causing a significant decrease in OLR.…”
Section: Introductionmentioning
confidence: 99%
“…The width of each arrow is proportional to the importance of that energy flow as compared to the amount of starlight that reaches the planet. This sort of schematic showing energy flows in a planet's atmosphere is sometimes called a Trenberth Diagram and are commonplace in climate studies of Earth and other worlds [7][8][9].…”
Section: The User Interfacementioning
confidence: 99%